DYNAMICAL (TIME-HARMONIC) AXISYMMETRIC STRESS FIELD IN THE PRE-STRETCHED NON-LINEAR ELASTIC BI-LAYERED SLAB RESTING ON THE RIGID FOUNDATION - Akbarov, S. D. (INST APPLIED MATHEMATICS, 2010)
Within the framework of the piecewise homogeneous body model with the use of the Three-dimensional Linearized Theory of Elastic Waves in Initially Stressed Bodies the axisymmetric dynamical stress field in the pre-stretched bi-layered slab resting on the rigid foundation is studied. It is assumed that the normal force which is located on a point and is time-harmonic acts on the free face plane of the slab. The elasticity relations of the layers' materials are described by the Murnaghan potential. The numerical results referring to the normal stress acting on the interface planes are presented for the pair of materials Aluminium 1915 and Acrylic Plastic.
Keywords: Bi-layered slab; initial strains; Hankel integral presentation; non-linear elastic; Murnaghan potential; time-harmonic stress field; Mathematics